KRAS RENAISSANCE(S) in Tumor Infiltrating B Cells in Pancreatic Cancer - Meng, Qingda; Valentini, Davide; Rao, Martin; Maeurer, Markus (Frontiers in Oncology, 2018)
KRAS is a driver mutation for malignant transformation, found in 30% of all cancers and in 90% of pancreatic cancer. The identification of small molecules inhibiting selectively KRAS mutants has been challenging, yet mutant KRAS has recently been shown to be targeted by tumor infiltrating T-cells that confer, upon adoptive transfer, tumor regression (Tran, NEJM, 375, 2255, 2016). A human IgG1 monoclonal antibody interfering with mutant KRAS function has been described (Shin, Nat. Comm. 8, 15090, 2017) to inhibit growth of KRAS mutant xenografts. B-cells have been described to infiltrate pancreatic cancer, they may be associated with TLS (tertiary lymphoid structures) associated with good prognosis - or to promote tumor growth. However, their function, nor their antigen-specificity has been defined. We discuss here the presence of tumor-infiltrating B-cells from patients with pancreatic cancer that produce KRAS-mutant specific IgG. This underlines that intra-tumoral T- and B-cells are able to exclusively target mutant KRAS and that KRAS – specific IgG that could be used as a blueprint for the construction of tumor-reactive chimeric antigen receptors (CARs), even if B-cells may promote tumor growth.